انعكاسات الالت ا زم البيئي على الأداء الاقتصادي للمؤسسات الصناعية - مؤسسة فرتيال نموذجا- - حريد ا رمي (Finance and Business Economies Review, 2023)
The integration of the environmental dimension in the management of industrial companies resulting from the end of the twentieth century through the implementation of environmental management systems (EMS). ISO 14001 is the reference model best known in this area. Under this standard, the implementation of an EMS is to improve the environmental performance of the company. This article attempts to clarify the point about the role of ISO 14001 in improving the overall performance of the Algerian industrial companies, through an exploratory study conducted among the industrial business unit Fertial-Annaba.